PERANAN KEBUDAYAAN RAMBU SOLO’ DALAM MENINGKATKAN PARIWISATA DI DESA KET’TE’ KESU’ KECAMATAN KESU’ - Randan, Gelardus Januarto Transenden; Kandowangko, Nicolas; Goni, Shirley Yvonne Viviane Irene (HOLISTIK, Journal Of Social and Culture, 2019)
Rambu Solo' is a traditional ceremony of the death of the Toraja society which aims at respecting and delivering deceased died towards the realms of the spirit, namely back to immortality along their ancestors in a resting place.Custom made by torajans has plenty of enticing tourists within the country and abroad who still looks liked a habit that smells of mystique as did by the Toraja ceremony in Rambu Solo'.What if the customs that are considered sacred simply becomes a free spectacle by the tourists who were present at the time of the ceremony to take place, not just a cultural role Rambu Solo' in concerned with the sustainability of the progress or of the the tourism. Because after all the custom Rambu Solo' identity is the Torajans who became the basis of the character of the local people.The role of the Government in the activities of the Rambu Solo' support the economy of the area although there are still many other elements that can support it. It can be said that there are no obstacles the Government participate in preserving Culture Rambu Solo'.Things that are very fundamental to the Toraja society especially in the village of Ke'te' Kesu’ yourself must be preserved so that this culture is not eroded by the times. There are still many elements from the aluk will always be enhanced by all elements of society and culture is expected to continue.Keyword: Rambu Solo', tourism, culture